Decolonizing Communication Studies. - Langmia, Kehbuma (Cambridge Scholars Publishing, 2022)
This volume examines the effects of the decolonization of communication studies. It shows that the discipline has undergone a rapid paradigm shift since the launching of the Ferment in the Field special edition of the Journal of Communication, in which scholars were called upon to rethink the field because of the crisis it was facing.